2012
DOI: 10.1093/icesjms/fss002
|View full text |Cite
|
Sign up to set email alerts
|

Cormorant diet in relation to temporal changes in fish communities

Abstract: Boström, M. K., Östman, Ö., Bergenius, M. A. J., and Lunneryd, S-G. 2012. Cormorant diet in relation to temporal changes in fish communities. – ICES Journal of Marine Science, 69: 175–183. The stomach contents of 229 great cormorants (Phalacrocorax carbo sinensis) shot between March and October 2009 along the Swedish east coast were analysed for differences in diet between gender, age, and breeding phase. Sticklebacks (Gasterosteus aculeatus and Pungitius pungitius) were the most common prey, followed by eelpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…The size ranges of perch and pikeperch eaten by cormorants agree with the results of previous studies where cormorants were found to prefer slender, 5-36 cm prey (Lunneryd and Alexandersson, 2005;Liordos and Goutner, 2007;Čech et al, 2008;Boström et al, 2012b). Looking at the whole prey size spectrum, the majority of consumed perch fall on the left hand side of the median, while most pikeperch fall to the right hand side of the median.…”
Section: Diet and Size Distributionsupporting
confidence: 89%
See 1 more Smart Citation
“…The size ranges of perch and pikeperch eaten by cormorants agree with the results of previous studies where cormorants were found to prefer slender, 5-36 cm prey (Lunneryd and Alexandersson, 2005;Liordos and Goutner, 2007;Čech et al, 2008;Boström et al, 2012b). Looking at the whole prey size spectrum, the majority of consumed perch fall on the left hand side of the median, while most pikeperch fall to the right hand side of the median.…”
Section: Diet and Size Distributionsupporting
confidence: 89%
“…For the birds in colonies located in these areas or near them, pikeperch is an important prey species. Lehikoinen (2005) and Boström et al (2012b) found few pikeperch in their study in the northern Baltic Sea, but Eschbaum et al (2003) found high quantities of pikeperch consumed by cormorants in the shallow areas (mean depth < 10 m) off the west coast of Estonia.…”
Section: Diet and Size Distributionmentioning
confidence: 90%
“…The diet study is based on several hundred stomachs from each area. But the interval of the relative contribution of some fish species to total biomass can be 50–100% of the estimated value [26]. Although the number of breeding birds is rather well documented we had to use estimates from other studies on number of foraging days of non-breeding and overwintering birds.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon these enrichment factors, cormorants seem to be feeding at least five levels above producers in this system, likely on piscivorous fish. Recent studies have shown that showing cormorants consume a variety of fish species, including large numbers of benthivores (which consume invertebrates as well as small fish) such as three-spine stickleback ( Gasterosteus aculeatus ), roach ( Rutilus rutilus ), and eelpout ( Zoarces viviparous ) as well as piscivorous predators (mostly perch ( Perca fluviatilis) ), though diet composition varies widely depending on the season and on local fish abundances [38], [39].…”
Section: Discussionmentioning
confidence: 99%